PRESENT-DAY SALT REGIME IN RESERVOIRS OF THE MANYCH RIVER BASIN - Matishov G.G.; Matishov D.G.; Gargopa Yu.M. (My University, 2006)
The reservoir system of the Manych River basin is located in the Kuma–Manych Depression of the southern Russian region, which is characterized by an arid climate, a shortage of water resources, and the development of salt marches and saline soils. The system extends in an almost latitudinal direction for a distance of over 300 km and includes the Proletarskoe (length 180 km, area 800 km2, volume 2 km3), Veselovskoe (length 90 km, area 250 km2, volume 0.8 km3), and Ust’Manych (length 60 km, area 70 km2, volume 0.1 km3) reservoirs. Their average depth ranges from 2.5 to 3.0 m. The system gives rise to natural–economic and social problems. Most important among these basins is Lake Manych-Gudilo, which represents a shallow relict marine basin in the Proletarskoe Reservoir.